A taxonomic revision of the Neotropical termite genus Cyrilliotermes Fontes (Isoptera, Termitidae, Syntermitinae). Zootaxa, 3186, 25–41. (Erratum) - Constantino, R.; Carvalho, S. H.c. (Zootaxa, 2012)
Erratum